2011
DOI: 10.1590/s0103-90162011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Sources and rates of potassium for sweet orange production

Abstract: Fruit yield and quality of citrus trees (Citrus spp.) is markedly affected by potassium (K) fertilization. Potassium chloride is the major source of K, even though other sources are also available for agricultural use when crops are sensitive to chloride or where potential for accumulation of salts in soils exists. Only few studies addressed the effect of K sources on yield and quality of citrus fruits. Therefore, the present study was conducted to evaluate K 2 SO 4 and KCl fertilizer sources at 0, 100, 200, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 22 publications
6
24
0
8
Order By: Relevance
“…According to Quaggio et al (2011), in order to achieve good CTF quality, perhaps K may be the most important element, since fruit yield and quality are largely influenced by potassium fertilization. Aular et al (2010) analyzed the relationship between soil and leaf K content and the characteristics of 'Valencia' orange fruit, and verified that soil K content was associated with rind and juice percentage.…”
Section: Macronutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Quaggio et al (2011), in order to achieve good CTF quality, perhaps K may be the most important element, since fruit yield and quality are largely influenced by potassium fertilization. Aular et al (2010) analyzed the relationship between soil and leaf K content and the characteristics of 'Valencia' orange fruit, and verified that soil K content was associated with rind and juice percentage.…”
Section: Macronutrientsmentioning
confidence: 99%
“…In addition, regardless of the source used, there was no K effect on yield, although it increased juice percentage and TA. Quaggio et al (2011) evaluated the effect of two K sources (K2SO4 and KCl) at doses of 0, 100, 200 and 300 kg ha -1 K2O per year on 'Pera' and 'Valencia' orange FQ and found that, with increasing K doses, there was a higher fresh fruit mass and SS decrease.…”
Section: Macronutrientsmentioning
confidence: 99%
“…The K may displace Mg from the exchange sites thereby increasing the content of the latter in the soil solution (Viade et al, 2011). The equilibrium of exchangeable cations in the soil is proportional to the activity ratio of K for divalent cations in soil solution (Quaggio et al, 2011). It was also determined that MgxK interactions in the soil due to magnesium fertilizing had negative effects on yield and quality properties.…”
Section: Resultsmentioning
confidence: 99%
“…According to the present study results, magnesium contents of hazelnut leaves were found little and middle. Quaggio et al (2011) reported that increased leaf K caused decreases on leaf Ca, Mg and B. The magnesium nutrition elements in kernels were changed from 0.15 to 0.17%.…”
Section: Resultsmentioning
confidence: 99%
“…Possivelmente, os baixos teores de K encontrados no solo sejam reflexos da ausência de adubações equilibradas nestas glebas. Este resultado sugere ser o K o elemento mais relevante para o manejo da adubação, por ser aquele cujo equilíbrio nutricional estaria sendo mais afetado, principalmente por ser um nutriente com conhecida resposta a sua aplicação em outras regiões (Quaggio et al 2011).…”
Section: Discussionunclassified